2017
DOI: 10.17984/adyuebd.310833
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship between Gender, Spatial Ability, Logical Reasoning Ability, and Preferred Mode of Processing

Abstract: The present study investigated the relationships between gender, spatial ability, logical reasoning ability, and preferred mode of processing. Data were collected from 107 prospective elementary teachers at a public university in Turkey. The results revealed that gender was unrelated to preference for visual or analytic processing suggesting that gender did not determine prospective teachers' preferred mode of processing. Moreover, Spatial ability was correlated with preference but the strength of the correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 25 publications
1
7
1
6
Order By: Relevance
“…In the studies by Abay, Tertemiz, and Gökbulut and Newcombe, it was revealed that there is no statistically significant difference between male and female teachers' spatial thinking skills (Abay, Tertemiz, & Gökbulut, 2018;Newcombe, 2013). Similarly, Hacıömeroğlu and Hacıömeroğlu could find no statistically significant difference between male and female elementary teachers' spatial thinking skills (Hacıömeroğlu & Hacıömeroğlu, 2017). However, some studies revealed that, male preservice teachers had higher levels of spatial thinking skills than females, and female preservice teachers had higher levels of anxiety than male preservice teachers (Dursun, 2010;Erkek, Işıksal, & Çakıroğlu, 2017;Ramirez, Gunderson, Levine & Beilock, 2012).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the studies by Abay, Tertemiz, and Gökbulut and Newcombe, it was revealed that there is no statistically significant difference between male and female teachers' spatial thinking skills (Abay, Tertemiz, & Gökbulut, 2018;Newcombe, 2013). Similarly, Hacıömeroğlu and Hacıömeroğlu could find no statistically significant difference between male and female elementary teachers' spatial thinking skills (Hacıömeroğlu & Hacıömeroğlu, 2017). However, some studies revealed that, male preservice teachers had higher levels of spatial thinking skills than females, and female preservice teachers had higher levels of anxiety than male preservice teachers (Dursun, 2010;Erkek, Işıksal, & Çakıroğlu, 2017;Ramirez, Gunderson, Levine & Beilock, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…It is the reality. However, gender is being widely investigated in terms of whether it is an influential factor on spatial thinking skills or not (Abay, Tertemiz, & Gökbulut, 2018;Dursun, 2010;Erkek, Işıksal, & Çakıroğlu, 2017;Hacıömeroğlu & Hacıömeroğlu, 2017;Maiorana, 2014;Newcombe, 2013;Vander Heyden, van Atteveldt, Huizinga, & Jolles, 2016). This is why we aimed to investigate gender as a factor for prospective preschool teachers.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that the findings obtained from the investigation of the variables affecting these skills will provide important contributions to teaching practices. Science reasoning test has been used in many researches to contribute science education vardır (Sökmen and Bayram, 1999;Ateş, 2002;Yenilmez, Sungur and Tekkaya, 2005;Sert Çıbık, 2006;Kılıç and Sağlam, 2009;Güler, 2010;Tuna, Biber and İncekapı, 2013;Aydın ve Kaptan, 2014;Turgut, Yenilmez and Balbağ, 2017;Hacıömeroğlu and Hacıömeroğlu 2017). The need to raise more qualified science and classroom teachers in the field of science education give a special importance to education faculties in global competitiveness environment.…”
Section: Extended Abstractmentioning
confidence: 99%
“…).Lawson Mantıksal Düşünme Testi dünyanın birçok ülkesinde özellikle fen alanlarında eğitim öğretime katkı sağlamak amacıyla pek çok araştırmada kullanılmıştır. Ülkemizde de bu testi kullanarak fen alanlarında öğretimin kalitesini geliştirmeye yönelik araştırmalar vardır(Ateş, 2002; Aydın ve Kaptan, 2014;Güler, 2010;Hacıömeroğlu ve Hacıömeroğlu 2017; …”
unclassified
“…Ülkemizde, görselleme, uzamsal görselleştirme konularında yapılan çalışmaların çoğu öğretmen adaylarıyla (Turgut & Yılmaz, 2012;Hacıömeroğlu & Hacıömeroğlu, 2017) yürütülen çalışmalardır. Öğrencilerle yapılan çalışmaların sayısı sınırlıdır.…”
Section: Introductionunclassified